Key Professional Competencies for Graduates in the Job Market: An Analysis of Employer Expectations in 2024 - Laura Timiras; Bogdan Nichifor; Luminița Zaiț; Aristița Rotilă; Oana Ancuța Stângaciu (Studies and Scientific Researches: Economics Edition)
This article presents some of the results of a study on the importance that employers attach to some of the professional competencies of university graduates, as well as on the level of satisfaction with graduates' competencies, respectively the need to improve them. The research was conducted at the level of a sample of 50 recruiters with reference to graduates of a higher education institution. The results of the research attest that for employers competencies such as: Teamwork, Specialized training – practical and theoretical, Communication Management of time, material resources and human resources, Critical and prospective thinking, Use of elements specific to digitization or information and communication technology are considered, on average, very important. It is also found that although they are satisfied or relatively satisfied with the competencies of graduates, employers consider it necessary for them to improve. This fact highlights the need for permanent improvement of employees' competencies as a way of adapting to the dynamics of the economic, social and technological environment in which organizations operate.